Comparison between conventional and digital dental impressions in pediatric patients: a narrative review - Montero-Gonzales, Dayana Isabel (2024)
In the following narrative review, original articles and review articles were collected from Pubmed, LILACS, ScienceDirect, SciELO, Scopus, and Google Scholar in the period between January 2013 and August 2023. Were selected 32 open access type published articles, in Spanish and English. Digital and conventional impressions in children are compared according to time, precision, handling, comfort, and acceptance. According to the evaluation criteria, it is concluded from the literature that digital impressions are the preferred choice in children. Therefore, taking digital impressions is favorable in terms of time, precision, handling, comfort and acceptance over conventional impressions in children.